Quest for the Phoenicians - Caragol, Pamela; Bredar, John B.; Cerveris, Michael; Zakin, Robert; Kane, David; Lyall, Robert (National Geographic Society special, 2006)
"Their sea-faring skills and vast trading network were the envy of the ancient world. But even today, the fabled Phoenicians remain a people shrouded in legend. Now, unravel a 3,000-year-old mystery as you join National Geographic on the Quest for the Phoenicians."--Container.